THE EFFECT OF COMPETENCE AND QUALITY OF WORK LIFE ON ORGANIZATIONAL CITIZENSHIP BEHAVIOR (OCB) WITH ORGANIZATIONAL COMMITMENT MEDIATION : Study on Jaken and Jakenan Health Center Employees - Sumarsi, Sumarsi; Rizal, Alimuddin (International Journal of Social and Management Studies, 2021)
The purpose of this study was to analyze the relationship between competence and quality of work life on organizational citizenship behavior by mediating organizational commitment.This research is a quantitative research, primary, data obtained from the answers to the questionnaires of each respondent using google form with data processing tools using SPSS software. The results of the questionnaire recapitulation got 104 respondents' answers, 102 respondents' answers were declared good for statistical data processing while 2 respondents' answers were not good so they were not included in the data processing.The population in this study were 106 employees with ASN status at Jaken and Jakenan health center. Based on the results of data analysis, it can be concluded that competence has a positive effect on organizational commitment to employees, quality of work life has a positive effect on organizational commitment to employees, competence has a positive effect on Organizational Citizenship Behavior, quality of work life has a positive effect on Organizational Citizenship Behavior, organizational commitment has no effect on Organizational Citizenship Behavior.